People participating in the 1986 y-Walk - Brock, Trish (photographer):::Creator::::::::::::
Negative shows a group of men and women participating in the 1986 y-Walk. Some of them are carrying balloons and some are wearing tee shirts that read: "Walk for women. YWCA 1986." They are walking past a building with a sign on it that reads: "Barclays Bank" at the corner of West Santa Clara Street and Market Street in downtown San Jose.